2020
DOI: 10.1002/ijfe.2075
|View full text |Cite
|
Sign up to set email alerts
|

Research on external financial risk measurement of China real estate

Abstract: This study applies the method proposed by Diebold and Yilmaz to construct a spillover effect index with which we compare the bilateral information spillover effect and time‐varying characteristics of China's real estate markets to those of representative international financial markets from July 2005 to March 2018 to measure the financial risks in China's real estate markets. The empirical results show the following. (a) There is a significant information spillover effect between China's real estate markets an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…The authors came to the conclusion that the faster cities recover from COVID-19 pandemic stress, and this conclusion was supported by an empirical study of a sample of new homes [2]. Jiang et al used the method suggested by Diebold and Yilmaz to create a spillover index to gauge the financial risk of the Chinese real estate market。 They came to the conclusion that after 2016, China's real estate financial risk entered a downward adjustment cycle, and real estate financial risk was significantly reduced [3]. Zhao put forward pertinent countermeasures and recommendations for the development of China's REITs in the post-epidemic era, and came to the conclusion that the growth of commercial real estate investment has changed the real estate market's vulnerable position, thereby enhancing the real estate market's risk resistance [4].…”
Section: Related Researchmentioning
confidence: 95%
“…The authors came to the conclusion that the faster cities recover from COVID-19 pandemic stress, and this conclusion was supported by an empirical study of a sample of new homes [2]. Jiang et al used the method suggested by Diebold and Yilmaz to create a spillover index to gauge the financial risk of the Chinese real estate market。 They came to the conclusion that after 2016, China's real estate financial risk entered a downward adjustment cycle, and real estate financial risk was significantly reduced [3]. Zhao put forward pertinent countermeasures and recommendations for the development of China's REITs in the post-epidemic era, and came to the conclusion that the growth of commercial real estate investment has changed the real estate market's vulnerable position, thereby enhancing the real estate market's risk resistance [4].…”
Section: Related Researchmentioning
confidence: 95%
“…There has been a developing trend of economic financialisaton in China in recent years (Xu and Xuan, 2021). The real economy sector on the one hand is facing an array of difficulties due to structural changes in market demand, overcapacity, rising costs and declining returns, whereas on the other hand, benefiting from the growth of financial and real estate industries (Jiang et al, 2021;Zhang et al, 2018). The widespread increasing importance of financial markets and financial institutions gave a boost to substantial risky investments in financial assets (Dore, 2008;Hahn, 2019).…”
Section: Family Firm Succession 2045mentioning
confidence: 99%
“…Lastly, we assemble a comprehensive set of factors as our control variables , including (1) average transaction price (Chinese Yuan per square meter) of new houses of city i in month t ( NP it ), (2) average transaction price (Chinese Yuan per square meter) of second-hand houses of city i in month t ( SP it ), (3) gross domestic product of city i in month t ( GDP it ), (4) per capita disposable income (Chinese Yuan) of residents of city i in month t ( INC it ), (5) consumer price index of city i in month t ( CPI it ), (6) net population migration rate (the difference between the number of immigrants and the number of emigrants over the total population) of city i in month t ( POP it ), (7) a linear time trend variable ( TND t ), indicating the time indicator (starting from one) of each month t and (8) a set of time dummies at the monthly level ( T t ). Control variables (1) and (2) are included because rental, new and second-hand housing markets could be correlated (Jiang et al , 2020; Zhai et al , 2018). Control variables (3) to (6) are macroeconomic and demographic factors, which are typical drivers of housing prices (Leung, 2004; Mulder, 2006).…”
Section: Model and Analysismentioning
confidence: 99%
“…Second, the rental, new and second-hand housing markets are typically correlated (Zhai et al , 2018; Jiang et al , 2020). For instance, when housing prices increase, more potential buyers may give up buying but switch to renting.…”
Section: Moderating Effectsmentioning
confidence: 99%